Herausforderungen bei der Realisierung des Museum of Fine Arts, Houston. Issue 1 (11th May 2018) - Schieber, Roman; Fildhuth, Thiemo; Oppe, Matthias; Helbig, Thorsten
Abstract : Challenges realizing the Museum of Fine Arts, Houston. Two new Steven Holl designed buildings are currently realized on the campus of the Museum of Fine Arts, Houston. The project with a total investment sum of 350 Mio USD is split into two phases; the so called "Glassell School" and the "Kinder Building". The main challenge on the first phase was the reduced architectural language of pure materiality which puts the concrete panels and large scale translucent glass units in show; what required minimal framing and joint dimensions. The windows with sizes of up to 8 m × 6 m have to withstand wind loads of up to 120 psf / 5.7 kN/m 2 . The actual Museum building will be enclosed with more than 1000 ∼ 6 m long translucent glass tubes. Besides the realization of the gravity‐bent glass; the precise control of daylight to the interior of the fine arts museum was one of the main challenges.